Protocol for a Nested Randomized Controlled Trial to Evaluate the Feasibility and Preliminary Efficacy of the Mindfulness Based Health Promotion Program on the Quality of Life of Older Adults Assisted in Primary Care—“The MBHP-Elderly Study” - Mapurunga, Marcelo Vasconcelos; Andreoni, Solange; de Oliveira, Daniela Rodrigues; Sarubbi, Vicente; Bonilha, Ana Cláudia; D'Almeida, Vania; Tomita, Luciana; Ramos, Luiz Roberto; Demarzo, Marcelo (Frontiers in Medicine, 2020)
INTRODUCTION: Population aging is a global phenomenon that has grown rapidly and progressively all over the world. Interventions that promote health must be studied and implemented to make the aging process be with quality of life. Depression and anxiety are the most common mental health conditions that compromise the quality of life on the elderly and it can cause damage to the autonomy and activities of daily life. Mindfulness training has been shown to improve psychological health and quality of life on adults. Studies involving Mindfulness-Based Interventions (MBIs) with older people are scarce in the literature, but they have been increasing in recent years showing promising results for healthy aging. This trial will investigate the feasibility and preliminary efficacy of an MBI on the quality of life of elderly assisted in the Primary Care. MATERIALS AND METHODS: A cohort-nested randomized controlled trial with 3 assessment points (baseline, post-intervention and one-year follow up) will be conducted to compare a MBI program (Mindfulness-based Health Promotion) to a cognitive stimulation control-group in a Primary Care facility. One-hundred and two older adults will be recruited from a cohort of this facility and they will be randomized and allocated into an intervention group (N=76) and the control group (N=76). The primary outcome evaluated will be the improvement of quality of life assessed by the WHOQOL-BREF and WHOQOL-OLD. The secondary outcomes will be cognitive function, psychological health, sleep quality, self-compassion, and religiosity. Qualitative data will be assessed by focus group and the word free evocation technique. The feasibility of the program will also be evaluated by adherence and unwanted effects questionnaires. DISCUSSION: This cohort-nested clinical trial will be the first mixed-methods study with 3 assessment points which will study the feasibility and preliminary efficacy of a mindfulness-based program for older people in Latin America population. If the findings of this study confirm the effectiveness of this program in this population it will be possible to consider it as intervention that might be implemented as public policy addressed to older people in healthcare systems. Trial registration: ClinicalTrials.gov, NCT03706807. Registered retrospectively on October 11th 2018.